2013
DOI: 10.1245/s10434-012-2834-0
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyosarcoma Management, Outcome, and Associated Molecular Biomarkers: A Single Institution’s Experience

Abstract: Background Uterine leiomyosarcoma (ULMS) is an aggressive, rapidly progressive tumor lacking clinical and molecular predictors of outcome. Methods ULMS patients (n = 349) were classified by disease status at presentation to MDACC as having intra-abdominal (n = 157) or distant metastatic disease (n = 192). Patient, tumor, treatment, and outcome variables were retrospectively retrieved. Formalin-fixed, paraffin-embedded tumor and control tissues from these patients (n = 109) were assembled in a tissue microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 33 publications
7
85
2
1
Order By: Relevance
“…The involvement of RB1 in pathogenesis of different malignancies as well as a role for RB1 in leiomyosarcoma is a frequent reported finding. [47][48][49] In contrast, a loss in 13q was only detected in a single leiomyoma indicating a potential use of intact RB as a surrogate marker for leiomyomas. Confirmation of this finding in a larger number and variety of leiomyomas is warranted.…”
Section: Discussionmentioning
confidence: 96%
“…The involvement of RB1 in pathogenesis of different malignancies as well as a role for RB1 in leiomyosarcoma is a frequent reported finding. [47][48][49] In contrast, a loss in 13q was only detected in a single leiomyoma indicating a potential use of intact RB as a surrogate marker for leiomyomas. Confirmation of this finding in a larger number and variety of leiomyomas is warranted.…”
Section: Discussionmentioning
confidence: 96%
“…No consensus has been reached regarding the correlation between the clinical course of LMS and possible prognostic factors such as age, disease stage, tumor size, necrosis, vascular invasion, and mitotic index (2,9,(15)(16)(17). Most studies reported that tumor size and mitotic index are the most significant parameters for prognosis (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Cases were evaluated for Ki-67 PI by dividing them into two groups on the basis of whether >10% or <10% staining was observed (15). For quantitatively evaluating Ki-67 staining, the five most intensively stained areas were selected while screening HPF at 40× magnification, and the average of these values was used (16).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Lusby ve ark. 'nın ça-lışmalarına göre 5 yılık sürvinin en çok bağımlı olduğu parametre ise intraperitonealrekürrens-tir (9). LMS'larda farklı prognostik parametreler rapor edilmiştir.…”
Section: Discussionunclassified